Fusion of the transcription factor TFE3 gene to a novel gene, PRCC, in t(X;1)(p11;q21)-positive papillary renal cell carcinomas - Weterman, Marian A. J. (The National Academy of Sciences of the USA, 1996)
The (X;1)(p11;q21) translocation is a recurrent chromosomal abnormality in a subset of human papillary renal cell carcinomas, and is sometimes the sole cytogenetic abnormality present. Via positional cloning, we were able to identify the genes involved. The translocation results in a fusion of the transcription factor TFE3 gene on the X chromosome to a novel gene, designated PRCC, on chromosome 1. Through this fusion, reciprocal translocation products are formed, which are both expressed in papillary renal cell carcinomas. PRCC is ubiquitously expressed in normal adult and fetal tissues and encodes a putative protein of 491 aa with a relatively high content of prolines. No relevant homologies with known sequences at either the DNA or the protein level were found.